The Social Impact of Michael Jackson’s ‘Heal the World’ on Youth Awareness - Alia Afifa; Jamaluddin Nasution; Citra Intan Christine Gea; Angel Herlin Chintya Harefa; Grace Asni Natalie Hulu; Mutiara Pia Gratia Situmorang (Teaching English and Language Learning English Journal, 2026)
This study aims to analyze the representation of humanistic values in Michael Jackson's song "Heal the World" and examine its contribution to public social awareness, particularly among today's youth. This study employs a qualitative, descriptive design. Data were collected through two primary sources: an analysis of the song's lyrics as the research object and an online questionnaire distributed to ten respondents from the current younger generation. Furthermore, a literature review is crucial to strengthening the theoretical foundation of this study. Data analysis techniques include content analysis, thematic analysis, and interactive analysis, encompassing data collection, simplification, presentation, and conclusion. The research findings indicate that the song conveys four humanistic values: empathy, social concern, peace, and optimism. The questionnaire results show that most young people are accustomed to enjoying the song without understanding its underlying meaning. However, a significant number of respondents acknowledged that the song conveys a humanistic message. The majority of respondents also believe that this song remains relevant to current conditions and influences their perspective on social issues. Additionally, nearly all respondents felt more compassionate toward others after listening to the song. However, this study also revealed a discrepancy between emotional impact and tangible actions, as only a few respondents were motivated to take direct positive action. This means the song's influence is more dominant in understanding and feelings than in actual actions. Thus, it can be concluded that the song "Heal the World" serves not only as mere entertainment but also as an effective medium for fostering social awareness among the younger generation. However, its influence on actual actions is still influenced by individual and environmental factors.